(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
تم إجراء البحث في المختبر لدراسة تأثير الزيت الصيفي (Kz oil 95% ) رشاً بتركيزين:0.5 و%1 حيث استهلك النبات الواحد 15 مل من سائل الرش والتعفير بالكبريت بمعدل0.75 غ / نبات على وضع بيض حافرة أوراق البندورة Tuta absoluta. استخدمت نباتات بندورة بعمر شهر مزروعة في أصص احتوى كل منها على نباتين اعتبرا مكرراً واحداً للمعاملة وكررت ثلاث مرات، ورشت نباتات الشاهد بالماء فقط. وضعت النباتات عشوائياً في ثلاثة أقفاص لتربية الحشرات حيث احتوى القفص الواحد على نباتات مكرر واحد للمعاملات (4 أصص). اتبعت الطريقة الاختيارية حيث تم إطلاق أربعة أزواج (ذكر وأنثى ) من بالغات الحشرة في القفص الواحد، وتم حساب عدد البيض الذي وضعته الإناث على كل نبات بعد 3 و6 و 10 أيام. أظهرت النتائج أن للزيت الصيفي ومسحوق الكبريت تأثيراً طارداً لوضع بيض حافرة أوراق البندورة الذي استمر ستة أيام حيث أدى الزيت الصيفي بالتركيزين 0.5 و 1 % إلى تخفيض عدد البيض بنسبة 59.45 و 76.95%على التوالي وأدى مسحوق الكبريت إلى التخفيض بنسبة 56.23% مقارنة مع الشاهد. وقد انخفض تأثير المركبات المختبرة بعد عشرة أيام. A laboratory experiment was conducted to examine the efficacy of summer oil (kz oil 95%) at concentrations 0.5 and 1% and sulfur dusting on oviposition of Tuta absoluta, where each plant consumed about 15 ml of spraying liquid and about 0.75 gr of sulphur. One month -old tomato plants in pots were used; each pot contained two plants considered one replicate of treatment and repeated three times. Control plants were treated with water only. Plants were placed randomizely in three cages each contained four pots, a replicate of all treatments. A choice test was carried out , where four pairs of adult insects (male and female) were released in each cage .The number of eggs laid by females was recorded in 3, 6 and 10 days after insects released. Results showed that all tested compounds had a repellent effect on oviposition of Tuta absoluta which continued 6 days after insects release, where the summer oil at concentration 0.5and 1% caused a decrease in eggs number 59.45 and76.95% respectively، and sulfur caused a decrease 56.23% compared with the control. The effect of tested compounds decreased in ten days.